2022
DOI: 10.3390/brainsci12020154
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Dysfunction, Headache, and Mental Clouding in Adults with Long-COVID-19: What Is the Link between Cognition and Olfaction? A Cross-Sectional Study

Abstract: Smell alteration and cognitive impairment are common features of the Long-COVID Syndrome. Mental clouding, often described as brain fog, might affect smell by altering recollection of odors or through a share mechanism of neuroinflammation. We investigated mental clouding, headache, and cognitive function in adult patients with persistent COVID-19 olfactory dysfunction. This multi-center cross-sectional study enrolled 152 adults with self-reported olfactory dysfunction from 3 tertiary centers specialized in CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 44 publications
5
51
1
1
Order By: Relevance
“…This is in line with results found in previous studies, revealing the association of olfactory and cognitive abilities in post COVID-19 patients [ 29 , 71 , 72 ]. In addition, it was also suggested that the more COVID-19 symptoms were more severe and persistent, such as olfactory impairment, the more cognitive impairment was higher [ 29 , 62 , 72 ]. Our results support this observation: the higher were TODA threshold scores, revealing deteriorated olfactory perception, the lower were PPTT scores.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is in line with results found in previous studies, revealing the association of olfactory and cognitive abilities in post COVID-19 patients [ 29 , 71 , 72 ]. In addition, it was also suggested that the more COVID-19 symptoms were more severe and persistent, such as olfactory impairment, the more cognitive impairment was higher [ 29 , 62 , 72 ]. Our results support this observation: the higher were TODA threshold scores, revealing deteriorated olfactory perception, the lower were PPTT scores.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have also shown an impairment of executive functions [ 20 , 25 , 28 , 29 , 30 , 31 , 32 , 33 ] attention [ 20 , 26 , 28 , 30 , 32 , 33 ] and memory [ 24 , 27 , 30 , 32 , 33 ] following COVID-19. In our study, we found that for the 40–59 age group, generative naming time was correlated with PPTT scores: the longer the generative naming time, the better the PPTT scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Headache, anosmia, and ageusia are frequent neurological symptoms. [9][10][11][12][13][14][15][16][17][18][19][20] Patients with Corona-19 virus disease (Covid-19) may present neurological symptoms with repercussions on imaging exams; and an association with ischemic infarction has been described 21,22 , as well as hemorrhagic lesions 23 , acute hemorrhagic necrotizing encephalopathy 24 , cerebral venous thrombosis 25 , and diffuse leukoencephalopathy with microhemorrhage. 26 Microhemorrhagic lesions and impregnation in the olfactory bulbs of patients with Covid-19 with or without anosmia have been described using the "coronal technique with thin T1 cuts with fat suppression in the anterior cranial fossa" pre-and post-contrast.…”
Section: Headache Associated With Covid-19 Infectionmentioning
confidence: 99%